Evaluasi Sistem Tata Kelola Limbah Medis Padat di RSUD Dr. Soetomo - Alis Suciyati (Universitas Airlangga, 2024)
Background: The hospital was a health service institution for the community. The impact was the operation of the hospital for to produce waste, including solid medical waste. This waste must be managed properly so as not to have a negative impact on the environment in the hospital. Objectives: This study aim was to provide an overview or evaluation of solid medical waste management at Dr Soetomo General Hospital compared to applicable regulations. Methods: Researchers used a qualitative descriptive research method using a systems approach (input, process and output). The data collection technique was carried out by interviews and questionnaires with qualitative data, from which the data was then quantified using a Likert scale to get a value and given weight, so that it would become quantitative data, with categories used for assessment, namely: good, if the score interval value > 89%, enough if the value of the interval score is > 40% to <80% and less if the value of the interval score is <40%. Results: The results showed evaluation of solid medical waste for the input section, there were 2 components that had less value, namely: methods and machines, for the process section, there were 5 components that had less value, namely the process of sorting, labeling, waste destruction, final disposal and procedures for treating solid medical waste). Conclusion: In the input and process components from the evaluation results had less value, improvement efforts are needed by compiling Standard Operational Procedure in accordance with current regulations, making repairs to incinerator machines that function less than optimally and carrying out socialization activities for officers in the process of managing solid medical waste in hospitals.